Hubungan Antar Stres Kerja dan Motivasi Kerja dengan Kinerja Perawat di Salah Satu Rumah Sakit Swasta di Bekasi : Literature Review - Pretty Merry Natalia; Elysabeth Sinulingga (Journal of Innovative and Creativity, 2025)
Job stress and work motivation are important forces that significantly affect nurse performance. High work demands, heavy workloads, an imbalance in the number of workers, and the complexity of services cause nurses to be vulnerable to work stress, which can lead to a decline in performance. Conversely, strong work motivation has great potential to improve nurse performance. This study aims to examine the relationship between work stress, work motivation, and nurse performance through a literature review approach. Research data was collected from Google Scholar using keywords such as nurse work stress, nurse work motivation, nurse performance, and hospital. The analysis results show that work stress has the potential to reduce performance, but in several other studies, this is inversely proportional, indicating that well-managed stress can actually improve performance. Work motivation is proven to be an important foundation that consistently encourages the improvement of nurse performance. The conclusion from this literature review confirms that both work stress and work motivation play a crucial role in nurse performance, where good motivation is able to reduce the negative impact of stress, so that nurse performance can be achieved optimally. Stress is a factor that will always arise, and each nurse's response varies, depending on their individual coping mechanism. Increasing motivation and effective stress management are the main keys in supporting the quality of nursing services in hospitals.